Escherichia coli O157:H7 Converts Plant-Derived Choline to Glycine Betaine for Osmoprotection during Pre- and Post-harvest Colonization of Injured Lettuce Leaves - Scott, Russell A.; Thilmony, Roger; Harden, Leslie A.; Zhou, Yaguang; Brandl, Maria T. (Frontiers in Microbiology, 2017)
Plant injury is inherent to the production and processing of fruit and vegetables. The opportunistic colonization of damaged plant tissue by human enteric pathogens may contribute to the occurrence of outbreaks of foodborne illness linked to produce. E. coli O157:H7 (EcO157) responds to physicochemical stresses in cut lettuce and lettuce lysates by upregulation of several stress response pathways. We investigated the tolerance of EcO157 to osmotic stress imposed by the leakage of osmolytes from injured lettuce leaf tissue. LC-MS analysis of bacterial osmoprotectants in lettuce leaf lysates and wound washes indicated an abundant natural pool of choline, but sparse quantities of glycine betaine and proline. Glycine betaine was a more effective osmoprotectant than choline in EcO157 under osmotic stress conditions in vitro. An EcO157 mutant with a deletion of the betTIBA genes, which are required for biosynthesis of glycine betaine from imported choline, achieved population sizes two-fold lower than those of the parental strain (P<0.05) over the first hour of colonization of cut lettuce in modified atmosphere packaging (MAP). The cell concentrations of the betTIBA mutant also were 12-fold lower than those of the parental strain (P<0.01) when grown in hypertonic lettuce lysate, indicating that lettuce leaf cellular contents provide choline for osmoprotection of EcO157. To demonstrate the utilization of available choline by EcO157 for osmoadaptation in injured leaf tissue, deuterated (D-9) choline was introduced to wound sites in MAP lettuce; LC-MS analysis revealed the conversion of D9-choline to D-9 glycine betaine in the parental strain, but no significant amounts were observed in the betTIBA mutant. The EcO157 ΔbetTIBA-ΔotsBA double mutant, which is additionally deficient in de novo synthesis of the compatible solute trehalose, was significantly less fit than the parental strain after their co-inoculation onto injured lettuce leaves and MAP cut lettuce. However, its competitive fitness followed a different time-dependent trend in MAP lettuce, likely due to differences in O2 content, which modulates betTIBA expression. Our study demonstrates that damaged lettuce leaf tissue does not merely supply EcO157 with substrates for proliferation, but also provides the pathogen with choline for its survival to osmotic stress experienced at the site